Nonuremic calciphylaxis in a post renal transplant patient - Maria Srour; Bahar Bastani (Society of Diabetic Nephropathy Prevention, 2019)
Background: Calciphylaxis is a potentially fatal condition previously observed in patients with poor renal function. We present a case of atypical presentation in a patient with good renal function after transplantation. Case Presentation: A-68-year old African American female with history of end-stage renal disease (ESRD) secondary to type II diabetes mellitus on hemodialysis for ten years, status post living related donor kidney transplant from her son three years prior to this presentation, parathyroidectomy, and atrial fibrillation on warfarin presented to our institution with progressively worsening, severely tender bilateral thigh lesions that were diagnosed as calciphylaxis. She was treated with sodium thiosulfate infusions for six months and continues to do well. Conclusions: Calciphylaxis, also known as calcific uremic arteriolopathy (CUA), has traditionally been associated with ESRD patients on maintenance dialysis, however several nonuremic cases of CUA have been reported in recent years. Multiple pathophysiologic mechanisms for CUA development have been proposed expanding the scope of known risk factors and possible triggers. CUA can be a life-threatening condition that is important for clinicians to recognize and treat as soon as possible.